2012
DOI: 10.1016/j.apal.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Abstract elementary classes and accessible categories

Abstract: We investigate properties of accessible categories with directed colimits and their relationship with categories arising from Shelah's Abstract Elementary Classes. We also investigate ranks of objects in accessible categories, and the effect of accessible functors on ranks.cardinals λ such that L is λ-categorical and, at the same time, a proper class of cardinals λ such that L is not λ-categorical.If this K has directed colimits then the categoricity conjecture fails for the class (4). By 4.12, however, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 8 publications
(57 reference statements)
3
83
0
Order By: Relevance
“…This weakens the GCH hypothesis in [BR12, 2.3(5)] and also shows (Remark 2.3) that sufficiently large presentability ranks are always successors if there is an ω 1 -strongly compact cardinal. Note that we could have obtained the result directly by carefully examining the proof in [BR12], but Theorem 3.10 is new and can be used even in situations where SCH does not hold (see Corollary 5.5).…”
Section: Presentability In Accessible Categoriesmentioning
confidence: 99%
“…This weakens the GCH hypothesis in [BR12, 2.3(5)] and also shows (Remark 2.3) that sufficiently large presentability ranks are always successors if there is an ω 1 -strongly compact cardinal. Note that we could have obtained the result directly by carefully examining the proof in [BR12], but Theorem 3.10 is new and can be used even in situations where SCH does not hold (see Corollary 5.5).…”
Section: Presentability In Accessible Categoriesmentioning
confidence: 99%
“…(7) Finally, for any Abstract Elementary Class in Shelah's sense, the class of structures and strong embeddings form an accessible category. The relation between AEC's and accessible categories has been investigated by several articles; see, for example, Beke-Rosický [6].…”
Section: Proposition 14 Supposementioning
confidence: 99%
“…Later Makkai and Paré [MP89] independently rediscovered these results and showed that they say essentially the same thing in different languages. The connection between AECs and accessible categories was then studied more closely by the first author [Lie11] and independently by Beke and the second author [BR12]. These works characterized AECs as special kinds of accessible categories with all directed colimits and whose morphisms are monomorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…This conjecture has profoundly shaped the development of the field (see the introduction of [Vas17a] for a survey and history of the conjecture). Note that Shelah's eventual categoricity conjecture can be rendered as a purely category-theoretic statement, with cardinalities replaced by presentability ranks-see [BR12,§6])-and hence can be posed in relation to general accessible categories.…”
Section: Introductionmentioning
confidence: 99%